A psychometric analysis of the workplace forgiveness scale - Itsara Boonyarit (2018)
Though there are measures of forgiveness published in the behavioural science literature, very few scales are available to measure forgiveness in workplace relationships. The Workplace Forgiveness Scale aimed to measure forgiveness of a specific offense. Data from 348 professional nurses in Thailand were subjected to an exploratory factor analysis (EFA) and the psychometric properties of the scale were examined. Results from EFA suggested retaining four underlying factors of the forgiveness construct: Overcoming Negative Thought and Feeling toward the Offender, Seeking to Understand the Offender's Reasons, Fostering Positive Approaches towards the Offender, and Belief in the Benefits of Forgiveness. Reliability coefficients for the total scale and subscales were adequate. Evidence of construct validity is presented. Scores on the forgiveness scale were positively associated with other related forgiveness constructs. Nomological validity analysis supported the theoretical networks of the forgiveness construct. Forgiveness played the complete mediating role in the relationship between dispositional forgiveness and willingness to reconcile, and played a partial mediating role in the relationship between rumination and seeking to revenge the offender. Bootstrap analysis on the parameter estimates of the sample results revealed satisfactory level of internal replicability and stability of the results across the samples. Implications for future research are discussed.